Translational Japanese: A Transformative Strangeness Within - Judy Wakabayashi (PORTAL: Journal of Multidisciplinary International Studies, 2009)
In 1813 Friedrich Schleiermacher proposed a ‘special domain just for translations’, where things not permitted elsewhere are allowed. Quite independently, Japanese society has reserved for translations a separate but not marginalized area that has even affected original writing. With its recognizably translational origin or influence, this language (hon’yakuch?) blurs the lines and hierarchy between translating and original writing, and also the source-target dichotomy. It traces back to encounters with Japan’s cultural ‘superiors’, China and the West, but today it stems from Japanese expectations toward translations as a genre, rather than the prestige of the source cultures. There is a belief that hon’yakuch? reflects the source text more transparently, allowing experience of the foreign, whereas rendering foreign texts into natural Japanese might give a sense of dislocation.

Tymoczko (2003: 201) argues that translators are not positioned in a ‘space between’—which would imply a lack of ideological engagement—but are inevitably committed to a particular cultural framework. Likewise, hon’yakuch? is not a neutral space between, but a site of engagement within the language proper. It would be inappropriate to describe translational Japanese as ‘foreignizing’ in the sense used by Venuti (1995), since it is not primarily motivated by a desire to disrupt readers’ complacency. Rather than constituting a locus of difference and respect for Otherness, hon’yakuch? represents a certain homogeneity in and of itself that does, nevertheless, help mediate between the foreign and the domestic.

Recently Japan’s growing cultural confidence has coincided with a shift toward domestication in translation, resulting in fewer opportunities to reorient the language through hon’yakuch?. Although it has become the target of some criticism and no longer strikes readers as fresh, it still has supporters and practitioners and continues to challenge the common Western conception of translationese as undesirable.